Perception of Graduate Students of Nepal towards Online Shopping - Poudel , R. (Pragya Darshan प्रज्ञा दर्शन, 2024)
The growing use of internet in Nepal provides a developing prospect for online shopping. This study focuses the variables or the factors on which graduate students keep in mind while shopping through online. This research deals with the perception of graduate students towards online shopping in Nepalese context. The theoretical model of this research was based on perceived usefulness, perceived ease of use, perceived risk and attitude of graduate students towards online shopping respectively. The theoretical model is also related to the online related lifestyle of graduate students. The study adopted the quantitative research design where data were collected through the distributed questionnaire. 300 samples of data were collected using electronic form (Google form). IBM SPSS (International Business Machine Statistical Package for Social Sciences) statistics 24 was used for the analysis of collected data. Descriptive analysis was conducted to describe and understand the feature specific data set where inferential statistics was employed to establish the relationship among the variables and to test the proposed hypothesis. The findings of the study showed that perception and attitude of graduate students towards online shopping is positive. There was also a significant relationship between perceived usefulness and attitude. There was significant relationship between perceived ease of use and attitude. Likewise there was significant relationship between perceived risk and attitude towards online shopping. Finally, the study provides insight for online related businessman and investors for the further development of online business.